Survival for oesophageal, stomach and small intestine cancers in Europe 1999–2007: Results from EUROCARE-5. Issue 15 (October 2015) - Anderson, L.A.; Tavilla, A.; Brenner, H.; Luttmann, S.; Navarro, C.; Gavin, A.T.; Holleczek, B.; Johnston, B.T.; Cook, M.B.; Bannon, F.; Sant, M.; EUROCARE-5 Working Group, 1
Abstract Background European regional variation in cancer survival was reported in the EUROCARE-4 study for patients diagnosed in 1995–1999. Relative survival (RS) estimates are here updated for patients diagnosed with cancer of the oesophagus, stomach and small intestine from 2000 to 2007. Trends in RS from 1999–2001 to 2005–2007 are presented to monitor and discuss improvements in patient survival in Europe. Materials and methods EUROCARE-5 data from 29 countries (87 cancer registries) were used to investigate 1- and 5-year RS. Using registry-specific life-tables stratified by age, gender and calendar year, age-standardised 'complete analysis' RS estimates by country and region were calculated for Northern, Southern, Eastern and Central Europe, and for Ireland and United Kingdom (UK). Survival trends of patients in periods 1999–2001, 2002–2004 and 2005–2007 were investigated using the 'period' RS approach. We computed the 5-year RS conditional on surviving the first year (5-year conditional survival), as the ratio of age-standardised 5-year RS to 1-year RS. Results Oesophageal cancer 1- and 5-year RS (40% and 12%, respectively) remained poor in Europe. Patient survival was worst in Eastern (8%), Northern (11%) and Southern Europe (10%). Europe-wide, there was a 3% improvement in oesophageal cancer 5-year survival by 2005–2007, with Ireland and the UK (3%), and Central Europe (4%) showing large improvements. Europe-wide, stomach cancer 5-year RS was 25%. Ireland and UK (17%) and Eastern Europe (19%) had the poorest 5-year patient survival. Southern Europe had the best 5-year survival (30%), though only showing an improvement of 2% by 2005–2007. Small intestine cancer 5-year RS for Europe was 48%, with Central Europe having the best (54%), and Ireland and UK the poorest (37%). Five-year patient survival improvement for Europe was 8% by 2005–2007, with Central, Southern and Eastern Europe showing the greatest increases (⩾9%). Conclusions Survival for these cancer sites, particularly oesophageal cancer, remains poor in Europe with wide variation. Further investigation into the wide variation, including analysis by histology and anatomical sub-site, will yield insights to better monitor and explain the improvements in survival observed over time.